Accrual-Based Accountability of Budgeting Realization Report in a Government Institution - Setiawan, Eko; Juanda, Ahmad; Leniwati, Driana (Ann Publisher, 2025)
Background. A system that can generate more accurate financial reports and other financial data, such as information on the government's financial performance, accountability, and situation, is required. Accrual-Based Government Accounting is a Government Accounting Standard that uses the APBD as a basis to recognize revenue, expenditure, and financing in budget implementation reporting, as well as revenues, expenses, assets, debts, and equity in accrual-based financial reporting. Aims. The purpose of this study is to comprehend how the new institutional analysis theory is applied. The demand for legal products drives changes in information technology. Methods. The author uses a qualitative descriptive method, analyzing the data through case studies, based on the organizational changes. Coercive isomorphism and normative isomorphism are two distinct phenomena that are indicated by the symptoms they exhibit. Result. In addition to reflecting current financial realities, including long-term liabilities, financial statements become increasingly thorough. The government can more fully display its rights and responsibilities by including its debts, receivables, assets, and expenses in addition to its financial inflows and outflows. Go ahead. Conclusion. Because financial data is more precise and comprehensive, the government can better plan and manage its finances. Regulatory changes, HR training, and the accounting information system all require updates. Implementation. A cost-benefit analysis allows the government to evaluate program performance in greater detail